2006
DOI: 10.1038/sj.npp.1301142
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Antipsychotic Drugs Directly Impair Insulin Action in Adipocytes: Effects on Glucose Transport, Lipogenesis, and Antilipolysis

Abstract: Treatment with second-generation antipsychotics (SGAs) has been associated with weight gain and the development of diabetes mellitus, although the mechanisms are unknown. We tested the hypothesis that SGAs exert direct cellular effects on insulin action and substrate metabolism in adipocytes. We utilized two cultured cell models including 3T3-L1 adipocytes and primary cultured rat adipocytes, and tested for effects of SGAs risperidone (RISP), clozapine (CLZ), olanzapine (OLZ), and quetiapine (QUE), together wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(114 citation statements)
references
References 35 publications
10
98
4
2
Order By: Relevance
“…On a peripheral level, it has been shown that olanzapine impairs insulin-stimulated glucose transport, increases lipogenesis and inhibits lipolysis in adipocytes (Vestri et al, 2006). Interestingly, a number of studies show evidence for acute, non-adiposity linked mechanisms (Houseknecht et al, 2005) and lack of correlation between weight gain and changes in glucose metabolism (Meyer, 2002;Lindenmayer et al, 2003;Simpson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…On a peripheral level, it has been shown that olanzapine impairs insulin-stimulated glucose transport, increases lipogenesis and inhibits lipolysis in adipocytes (Vestri et al, 2006). Interestingly, a number of studies show evidence for acute, non-adiposity linked mechanisms (Houseknecht et al, 2005) and lack of correlation between weight gain and changes in glucose metabolism (Meyer, 2002;Lindenmayer et al, 2003;Simpson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…OLZ may influence hormones associated with the regulation of insulin and/or glucose (Vestri et al, 2007). The typical clinical path toward diabetes is associated with increased adiposity and subsequent changes in insulin sensitivity; however, the rapid onset of diabetes associated with SGA administration, and the disappearance of hyperglycemia after discontinuation in patients suggests that the development of diabetes in patients on SGAs may be an acute drug-related effect (Rettenbacher et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that OLZ has direct effects on glucose regulation, possibly leading to hyperinsulinemia, hyperglycemia, and insulin resistance (Baptista et al, 2002;Graham et al, 2005;Melkersson and Hulting, 2001;Seemuller et al, 2005). Of note, recent experiments show that SGAs may impair both the insulinresponsive glucose transport system, as well as lipolysis in adipocytes (Vestri et al, 2007), demonstrating that antipsychotic drugs may differentially affect insulin action and metabolism through direct cellular effects in adipocytes. OLZ has also been associated with acute insulin resistance following a single dose in healthy animals (Houseknecht et al, 2007), emphasizing the need for therapies aimed at managing unwanted metabolic side effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, a major side effect of SGAs is the development of symptoms similar to type 2 diabetes [1][2][3][4][5]. It is widely assumed that this is caused by peripheral insulin resistance following excessive weight gain observed with people prescribed these drugs [6][7][8].…”
Section: Introductionmentioning
confidence: 99%